2013
DOI: 10.1038/clpt.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacogenetics Implementation Consortium Guideline for CYP2D6 and CYP2C19 Genotypes and Dosing of Tricyclic Antidepressants

Abstract: nature publishing groupPolymorphisms in CYP2D6 and CYP2C19 affect the efficacy and safety of tricyclics, with some drugs being affected by CYP2D6 only, and others by both polymorphic enzymes. Amitriptyline, clomipramine, doxepin, imipramine, and trimipramine are demethylated by CYP2C19 to pharmacologically active metabolites. These drugs and their metabolites, along with desipramine and nortriptyline, undergo hydroxylation by CYP2D6 to less active metabolites. Evidence from published literature is presented fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
360
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(374 citation statements)
references
References 39 publications
7
360
0
7
Order By: Relevance
“…In this context, one important point of our study is the exploratory pharmacological analysis performed to test the correlation between AHI and DMI plasma concentrations. In several studies, inter‐individual differences in side effects and treatments responses have been associated with variability of tricyclic drug plasma concentrations 27. Our clinical trial also showed the intervariability of DMI plasma concentrations between treatment groups (DMI low and high dose) and the intravariability of DMI within each treatment group.…”
Section: Discussionsupporting
confidence: 69%
“…In this context, one important point of our study is the exploratory pharmacological analysis performed to test the correlation between AHI and DMI plasma concentrations. In several studies, inter‐individual differences in side effects and treatments responses have been associated with variability of tricyclic drug plasma concentrations 27. Our clinical trial also showed the intervariability of DMI plasma concentrations between treatment groups (DMI low and high dose) and the intravariability of DMI within each treatment group.…”
Section: Discussionsupporting
confidence: 69%
“…Based on the statistically phased genotypes, we determined that NA12878 possesses both the *3 and *4 loss-of-function alleles for CYP2D6 , and this *3/*4 diplotype is interpreted as reduced metabolism of drugs such as codeine (an opiate) and olanzapine (an atypical antipsychotic) 2022 .…”
Section: Resultsmentioning
confidence: 99%
“…Several antidepressants used to treat these disorders are either metabolized exclusively by CYP2C19 or CYP2D6, or by a combination of these enzymes. The relevance of these enzymes is exemplified by the recent publication of guidelines for their use in defining TCA dosage regimens [51].…”
Section: Cyp2c19 Cyp2d6 and The Management Of Major Depressive Disormentioning
confidence: 99%